Eruption and caries status of first permanent molars in children aged 6-7 years in Shijingshan District, Beijing, China - Mei Zhao; Zhaoyou Wang; Min Liu; Ziqi Song; Rong Wang; Lina Yang (BMC, 2024)
Abstract Background Dental caries is still a major disease that affect the oral health of people in China. First permanent molars (FPMs) are the most caries-susceptible teeth among school-aged children. The aim of this study was to investigate the eruption and caries status of first permanent molars in children aged 6-7 years in Shijingshan District, Beijing, China, to provide information for oral health promotion. Methods The study was a cross-sectional survey conducted in 6-7-year-old first grade children from public elementary schools in Shijingshan District, Beijing. Participants were invited to receive a clinical oral examination. The eruption status and caries experience of FPMs were recorded. Questionnaires assessing children's sociodemographic information and oral health-related behaviors were completed by the children's parents or guardians. Results A total of 3,176 children, including 1,644 boys (51.8%) and 1,532 girls (48.2%) were included in the oral examination and questionnaire. Eruption status of FPMs was as follows: 37.5% fully erupted, 28.3% partially erupted, 34.2% not erupted. Girls had more erupted FPMs than boys (70.1% VS 61.8%, P < 0.001). The prevalence of dental caries in FPMs was 5.5% (174/3,176) in studied children. The mean decayed missing filled teeth score of FPMs was 0.11 and the mean decayed missing filled surface score of FPMs was 0.19. Binary Logistic regression analysis demonstrated that girls had more tooth decay than boys and father's educational background also associated with the caries experience of the studied children (P < 0.05). Conclusions Around two-thirds of FPMs were fully erupted or partially erupted among children aged 6-7 years old in Shijingshan District, Beijing. Approximately 5% of the newly erupted FPM established dental caries. Effective intervention should be applied in this age group for oral health promotion.